PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Manik, Vitaloka; Manurung, Amran; Saribu, Ardin Dolok (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the effect of profitability proxied by Return on Equity (ROE) on firm value proxied by Price to Book Value (PBV) in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research employs a quantitative approach using linear regression analysis. The results indicate that ROE has a significant effect on PBV with a significance level of 0.004 (<0.05), thus the hypothesis is accepted. These findings suggest that profitability remains an important signal for investors in evaluating firms. However, the negative regression coefficient reveals an anomaly where an increase in ROE is not always followed by an increase in firm value. This condition is influenced by external factors, investor preferences for dividends, and the defensive nature of the industry. Therefore, investors’ valuation is not solely based on earnings performance but also considers risk factors and long-term prospects.